1989
DOI: 10.1128/jcm.27.8.1782-1786.1989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aeromonas sobria hemolysin by use of monoclonal antibodies against Aeromonas hydrophila hemolysins

Abstract: Aeromonas sobria produces hemolysin in a form activable with trypsin under defined cultural conditions. In immunoblotting analyses with the culture supernatant of A. sobria, the monoclonal antibody reacting specifically to Aeromonas hydrophila CA-11 hemolysin bound to the 53,000and 49,000-dalton bands before and after trypsinization, respectively. The monoclonal antibody reacting to A. hydrophila AH-1 hemolysin did not bind either band. A. sobria hemolysin is, therefore, related antigenically to CA-11 hemolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…These results correlated with data from studies of A. sobria and A. hydrophila hemolysins, which also required trypsinization before the hemolysin could be activated (Kozaki et al, 1989). To demonstrate that this hemolytic activity was not associated with Act, the culture supernatant of wild-type A. hydrophila SSU strain as well as from the act-minus mutant was subjected to neutralization with Act-specific antibodies.…”
Section: Hemolytic Activity and Neutralization Testsupporting
confidence: 75%
See 1 more Smart Citation
“…These results correlated with data from studies of A. sobria and A. hydrophila hemolysins, which also required trypsinization before the hemolysin could be activated (Kozaki et al, 1989). To demonstrate that this hemolytic activity was not associated with Act, the culture supernatant of wild-type A. hydrophila SSU strain as well as from the act-minus mutant was subjected to neutralization with Act-specific antibodies.…”
Section: Hemolytic Activity and Neutralization Testsupporting
confidence: 75%
“…The HlyA protein did not exhibit any homology with other hemolysins or the aerolysin and act genes that were cloned and characterized earlier from several Aeromonas spp. (Kozaki et al, 1989;Wong et al, 1998;Wang et al, 2003;Yu et al, 2005;Galindo et al, 2006b). However, the hlyA gene is present on the genome of A. hydrophila ATCC 7966 strain that was recently sequenced (GenBank accession number CP000462) (Seshadri et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Kozaki et al reported that a monoclonal antibody against the hemolysin of A. hydrophila neutralizes the enterotoxic activity of the culture supernatant of A. sobria, indicating that the hemolysin of the latter also possesses enterotoxic activity (18). Subsequently, Millership et al examined the effects of A. sobria culture filtrates containing defined levels of hemolysin and CT immunoreactivity on water and ion flux in the gut by means of a modified rat jejunal perfusion assay.…”
mentioning
confidence: 99%
“…hydrophila. Kozaki et al (17) proved that hemolysin produced by A. sobria caused fluid accumulation in infant mouse intestine. More recently, A. schubertii was isolated from human wounds and characterized as causing primary cellulitis (6) .…”
mentioning
confidence: 99%